Proceedings of the 2020 International Conference on Multimodal Interaction 2020
DOI: 10.1145/3382507.3418837
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Laboratory and Wearable Sensors in the Context of Physiological Synchrony

Abstract: Measuring concurrent changes in autonomic physiological responses aggregated across individuals (Physiological Synchrony -PS) can provide insight into group-level cognitive or emotional processes.Utilizing cheap and easy-to-use wearable sensors to measure physiology rather than their highend laboratory counterparts is desirable. Since it is currently ambiguous how different signal properties (arising from different types of measuring equipment) influence the detection of PS associated with mental processes, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Classifying a single participant into one of the two instructional groups could be done with 96% accuracy when using synchrony of EEG, and with 73% accuracy when using heart rate and skin conductance. In addition, the reliability of the wearable data that were collected with equipment suitable for real-life settings was similar to the reliability of laboratory equipment ( Van Beers et al, 2020 ), and we observed physiological synchrony in skin conductance and heart rate recorded through wearables in actual classroom settings ( Stuldreher et al, 2021 ). Directly comparing experimental laboratory equipment with equipment suitable for real-life settings form a crucial step in tackling issues around the technical limits to use neurocognitive measures in classroom settings ( evaluation ).…”
Section: The Neurolabnl Startimpulse Project: Optimal Conditions For Education and Social Safety Of Youthsupporting
confidence: 65%
“…Classifying a single participant into one of the two instructional groups could be done with 96% accuracy when using synchrony of EEG, and with 73% accuracy when using heart rate and skin conductance. In addition, the reliability of the wearable data that were collected with equipment suitable for real-life settings was similar to the reliability of laboratory equipment ( Van Beers et al, 2020 ), and we observed physiological synchrony in skin conductance and heart rate recorded through wearables in actual classroom settings ( Stuldreher et al, 2021 ). Directly comparing experimental laboratory equipment with equipment suitable for real-life settings form a crucial step in tackling issues around the technical limits to use neurocognitive measures in classroom settings ( evaluation ).…”
Section: The Neurolabnl Startimpulse Project: Optimal Conditions For Education and Social Safety Of Youthsupporting
confidence: 65%
“…EDA and heart rate were also recorded using wearable systems (Movisens EdaMove 4 and Wahoo Tickr, respectively). These data are discussed elsewhere ( Borovac et al, 2020 ; Van Beers et al, 2020 ).…”
Section: Methodsmentioning
confidence: 78%
“…Examples of products in this industry are wrist and headbands to monitor and reduce own stress levels, or gadgets to detect mood for entertaining purposes. A trending subfield in scientific studies and industry are tools to modulate brain activity directly through neurostimulation (Tyler et al, 2017;Vosskuhl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%